Realpolitik Ideology : Indonesia's Use of Military Force - Sebastian, Leonard C. (Book collections on Project MUSE., 2006)
Realpolitik Ideology represents path-breaking research on the Indonesian military (TNI) going beyond traditional scholarship on the TNI's dual function or dwifungsi which has been one of the dominating fields of analysis in Indonesian studies since the 1970s. Addressed to political scientists, sociologists, historians, anthropologists and defence practitioners, this book interprets security policy in terms of its social roots asserting that the realpolitik behaviour of the TNI has strong "socio-cultural" undertones, which in turn shape the development of military doctrine. The argument made in the book is that only through a better understanding of the doctrines that reinforced the military's significant presence in Indonesian affairs and their subsequent restructuring can Indonesia's policy-makers attempt meaningful reform of the TNI.